PENGARUH SOCIAL MEDIA MARKETING DAN PROMOSI TERHADAP MINAT BELI KONSUMEN DITOKO ONOY BAKERY ARIZONA JAMBI - Pangestu, Mira Gustiana; Sabrina, Hanan Laras; Yossinomita; Ramadhan, Raihan Fajri (Journal of Business Studies and Management Review, 2025)
This study explores the influence of social media marketing and promotional strategies on consumer purchase intention at Onoy Bakery in Arizona, Jambi. In today’s highly competitive bakery industry, digital marketing plays a crucial role in attracting consumer interest. The research was conducted by gathering insights from consumers through questionnaires. The findings reveal that social media marketing has a strong impact on consumers' willingness to make a purchase, particularly through the use of engaging visual content, interactive communication, and platforms such as Instagram and TikTok. On the other hand, traditional promotional methods did not appear to significantly affect consumer interest. These results highlight that while social media marketing is an effective tool for increasing purchase intention, conventional promotional strategies may require further innovation to remain relevant. This study underscores the importance for businesses to adapt to digital trends in order to maintain consumer engagement and drive purchasing decisions.